Material selection, characterization, optimization, and usability of bio-composites using fused deposition modelling - Che Hamid, Hazliza Aida (2025)
This research examines the material selection, characterization, optimization, and usability of bio-composites in additive manufacturing (AM). Development of environmentally sustainable egg carton packaging is used as case study and fabricate using Fused Deposition Modelling (FDM). The case study comprises of four primary phases: identifying appropriate bio-composite filament materials, characterizing their mechanical and printing characteristics, optimizing FDM settings, and assessing the usability of the final egg carton prototype. The Fuzzy Analytic Network Process (FANP) identified polylactic acid (PLA) reinforced with 7.5 wt.% sugar palm fibre (SPF) as the ideal material. The SPF-PLA composite containing 7.5 wt.% SPF was selected as the optimum material in this study, owing to its superior mechanical strength, printability, environmental sustainability, and processing stability, as corroborated by both FANP ranking and experimental validation. The printing settings were first optimized by the Taguchi technique, establishing optimal circumstances of 0.1 mm layer thickness, 100% infill density, and a print speed of 25 mm/s to guarantee better print quality and structural integrity. Mechanical and physical evaluations validated the printability and efficacy of the SPF-PLA composite. A functioning egg carton prototype was then produced using FDM based on these proven features. Usability testing was performed with 10 volunteers using the System Usability Scale (SUS), in which participants evaluated 10 assertions on a Likert scale. The findings produced an average SUS score of 80, categorizing the prototype as good within the 4th quartile range. Participants expressed positive opinions about the carton’s durability, usability, and environmental benefits. The results confirm the SPF-PLA bio- composite as a feasible material for sustainable egg carton packaging and illustrate the potential of FDM technology for scalable, environmentally responsible production.